A UNIQUE WORK EXCITED THE LEADING MINDS OF THE EUROPEAN LATE RENAISSANCE - Shadmanov K. B. (Modern American Journals, 2026)
As is known, the perception and assimilation of the cultural and creative heritage of other peoples is part of a broader intercultural dialogue, both intellectual, ideological, and moral and aesthetic aspects of the process of interethnic mutual knowledge. Acquaintance with the unique didactic and pedagogical heritage of the great representatives of England of the XYII century, with its content and philosophy, should perhaps begin with the artistic creation of Francis Bacon and his rare work "The Essays or counsels, civil and moral", which has become one of the favorite and valuable for readers all over the world. In the article, the author reflects on one of the unique figures of the English late Renaissance, Francis Bacon, an outstanding philosopher, statesman and thinker, an author who made an invaluable contribution to the development of the essay genre in the literature and philosophy of the European Renaissance. His “The Essays, or Counsels, Civil and Moral” is considered one of the valuable and rare works of English literature. This article is devoted to the study of the unique thoughts expressed by the great thinker in this literary source. The author attempted to share the philosophical and moral ideas of the English thinker, aimed at the worthy education of the younger generation.
Keywords: Renaissance, essay, rhetoric, classical text, philosophical style, cultural thought.